The Unrules - Tulchinsky, Igor (Ascent Audio, 2019)
Learn from a master of quantitative finance the rules that made him a success. The UnRules presents the dynamic rules for success in the age of exponential information. Written by Igor Tulchinsky, the trader behind global quantitative investment management firm WorldQuant, this book is more than just another Big Data guide for financial wonks-it's a prescriptive, inspirational book for everyone navigating the tidal waves of the information age. Data is everywhere, coming at us in a never-ceasing, ever-rising river that threatens to overwhelm us. Tulchinsky shows us, however, how natural patterns underlie that data-patterns that may dictate life or death, success or failure. The marriage of man and machines has allowed scientists to explore increasingly complex worlds, to predict outcomes and eventualities. This book demonstrates how to exercise real intelligence by discerning the patterns that surround us every day and how to leverage this information into success in the workplace and beyond.
Online resource; Title from title page (viewed January 25, 2019)
Keywords: Tulchinsky, Igor -- 1966-; Success in business; Business; Information society; Information technology; Strategic planning; Succès dans les affaires; Affaires; Société informatisée; Technologie de l'information; Planification stratégique; information technology; Audiobooks